Structural adhesive, preparation method thereof and wind power blade

By using hydrophilic vapor phase silica and thixotropic agent in the structural adhesive of wind power blades, the problems of poor bonding interface performance and high cost in the prior art are solved, and higher tension pressure is achieved Fatigue performance and lower cost.

CN119242237AInactive Publication Date: 2025-01-03SINOMATECH WIND POWER BLADE
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411505319.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The structural glue used in existing wind power blades uses hydrophobic or ordinary vapor phase silica as thixotropic agents, resulting in poor bonding interface performance and high cost, and is prone to cracking during tensile fatigue.

Method used

The hydrophilic vapor-phase silica thixotropic agent and aided thixotropic agent are used to adjust their proportions to improve the pulling and shearing performance of the structural glue and reduce the cost of the structural glue. The specific method includes adding a thixotropic agent, a silane coupling agent and a hydrophilic vapor-phase silica to component A, forming a synergistic effect through multiple dispersion treatments, and improving the performance of the thixotropic agent.

Benefits of technology

The tension fatigue performance and tensile stress amplitude of structural adhesives are significantly improved, the total content of silica is reduced, thereby reducing the overall cost of structural adhesives and improving the bonding interface performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242237A_ABST
    Figure CN119242237A_ABST
Patent Text Reader

Abstract

The invention discloses a structural adhesive and a preparation method thereof and a wind turbine blade, the structural adhesive comprises a component A and a component B, the mass ratio of the component A to the component B in the structural adhesive is 100: (35-45), and based on the total mass of the component A, the component A comprises 1 wt%-2 wt% of an assistant thixotropic agent, 0.8 wt%-1.2 wt% of a silane coupling agent, 2.5 wt%-3 wt% of hydrophilic fumed silica and the balance of components. The hydrophilic fumed silica is adopted in the structural adhesive, a good synergistic effect is generated after the proportion of the hydrophilic fumed silica, the silane coupling agent and the auxiliary thixotropic agent is adjusted according to the proportion of the structural adhesive, the tensile shear performance of the structural adhesive can be improved, meanwhile, compared with at least 8 wt% of silicon dioxide in an existing structural adhesive, the tensile shear performance of the structural adhesive is improved, and the tensile shear performance of the structural adhesive is improved. The silicon dioxide content is low, and the overall cost of the structural adhesive can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wind power generation, and in particular relates to a structural adhesive and a preparation method thereof, and a wind power blade. Background Art

[0002] At present, in the field of wind power, structural adhesive is generally used as adhesive in the mold bonding process during the manufacturing process of wind turbine blades. Structural adhesive is also generally called "mold bonding adhesive". Most of the structural adhesives used for blades are epoxy structural adhesives based on epoxy resin. Epoxy structural adhesives usually include components A and B, among which component A currently uses hydrophobic fumed silica or ordinary fumed silica as a thixotropic agent.

[0003] The existing structural adhesive has poor bonding interface performance and high cost in the use of wind turbine blades because its A component uses hydrophobic fumed silica or ordinary fumed silica as a thixotropic agent. Summary of the invention

[0004] The embodiments of the present invention provide a structural adhesive and a preparation method thereof, and a wind turbine blade. Component A of the structural adhesive of the present application adopts a relatively low content of a hydrophilic fumed silica thixotropic agent and a thixotropic aid, which improves the tensile shear properties of the structural adhesive while reducing the cost of the structural adhesive.

[0005] In a first aspect, a structural adhesive is provided, comprising a component A and a component B, wherein the mass ratio of component A to component B in the structural adhesive is 100:(35-45), wherein, based on the total mass of component A, component A comprises a thixotropic agent: 1wt%-2wt%; a silane coupling agent: 0.8wt%-1.2wt%; a hydrophilic fumed silica: 2.5wt%-3wt%; and other components.

[0006] In a first possible implementation, the hydrophilic fumed silica is hydroxyl-modified fumed silica; the tensile-compression fatigue m value of the structural adhesive is ≥12.5, and / or, when the number of cycles is tens of millions, the tensile stress amplitude of the structural adhesive is ≥56 MPa.

[0007] In combination with the above possible implementations, in a second possible implementation, the silane coupling agent is KH560; and / or the thixotropic agent is a polyhydroxy compound, preferably, the thixotropic agent is one or more of trimethylolpropane propylene glycol ether, ethylene glycol, diethylene glycol, glycerol, triethylene glycol, tetraethylene glycol, and dipropylene glycol.

[0008] In combination with the above possible implementations, in a third possible implementation, based on the total mass of component A, component A may also include bisphenol A epoxy resin: 55wt% to 60wt%; bisphenol F epoxy resin: 28wt% to 33wt%; diluent: 7wt% to 13wt%.

[0009] In combination with the above possible implementations, in a fourth possible implementation, the bisphenol A epoxy resin is a low molecular weight bisphenol A epoxy resin, preferably, the low molecular weight bisphenol A epoxy resin is bisphenol A diglycidyl ether; and / or, the bisphenol F epoxy resin is a low molecular weight bisphenol F epoxy resin, preferably, the low molecular weight bisphenol F epoxy resin is bisphenol F diglycidyl ether; and / or, the diluent is a glycol diglycidyl ether, preferably, the diluent is butanediol diglycidyl ether and / or cyclohexanediol diglycidyl ether.

[0010] In combination with the above possible implementation methods, in a fifth possible implementation method, based on the total mass of component B, component B includes polyetheramine: 30wt% to 32wt%; amino polyamide: 20wt% to 22wt%; heat-resistant amine-IPDA: 11wt% to 13wt%; toughening agent: 29wt% to 31wt%; fumed silica: 4wt% to 6wt%.

[0011] In combination with the above possible implementations, in a sixth possible implementation, the polyetheramine is a polyetheramine with a functionality ≥ 4, preferably D230 and / or T403; and / or the toughening agent is one or more of a core-shell polymer toughening agent, a carboxyl-terminated nitrile rubber, an amino-terminated nitrile rubber, an amino-terminated polyether (high molecular weight polyetheramine), an amino-terminated butyl rubber or a polyurethane toughening agent, preferably polyetheramine T-5000; and / or the fumed silica is a hydrophilic fumed silica.

[0012] In a second aspect, a method for preparing a structural adhesive is provided, wherein component A is prepared by the following method:

[0013] The thixotropic agent, silane coupling agent and other components in component A are mixed evenly to obtain a mixture;

[0014] The hydrophilic fumed silica is added to the mixture several times to disperse and obtain component A.

[0015] In a first possible implementation, hydrophilic fumed silica is added to the mixture in multiple times for dispersion treatment, and in the step of obtaining component A, the mass of hydrophilic fumed silica added each time does not exceed 0.3% of the total mass of component A; and / or, after each addition of hydrophilic fumed silica, dispersion treatment is performed, and the next addition of hydrophilic fumed silica is performed after sufficient dispersion.

[0016] In a third aspect, a wind turbine blade is provided, wherein the structural adhesive of the first aspect is used in the preparation process of the wind turbine blade and / or the structural adhesive prepared by the preparation method of the second aspect is used in the preparation process.

[0017] Compared with the prior art, the structural adhesive provided in the embodiment of the present application uses hydrophilic fumed silica, and the ratio of hydrophilic fumed silica, silane coupling agent and auxiliary thixotropic agent is adjusted to auxiliary thixotropic agent: 1wt%~2wt%, silane coupling agent: 0.8wt%~1.2wt%, hydrophilic fumed silica: 2.5wt%~3wt%, which produces a good synergistic effect, which can improve the tensile shear performance of the structural adhesive. At the same time, compared with at least 8wt% of silica in the existing structural adhesive, the silica content of the present application is lower, which can reduce the overall cost of the structural adhesive. Among them, the auxiliary thixotropic agent can help or promote the thixotropy of the hydrophilic fumed silica and bridge between the thixotropic agents to increase the performance of the thixotropic agent. The large number of hydrophilic functional groups on the surface of the hydrophilic fumed silica can form a large number of hydrogen bonds with the epoxy resin to improve the performance of the structural adhesive. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments of the present invention are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 Schematic diagram of the structure of hydrophilic fumed silica according to one embodiment of the present invention. DETAILED DESCRIPTION

[0020] The features and exemplary embodiments of various aspects of the present invention will be described in detail below. In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only intended to explain the present invention, rather than to limit the present invention. For those skilled in the art, the present invention can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present invention by illustrating examples of the present invention.

[0021] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.

[0022] The above-mentioned inventive content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates an exemplary embodiment. In many places throughout the application, guidance is provided by a series of embodiments, which can be used in various combinations. In each example, the enumeration is only a representative group and should not be interpreted as exhaustive. In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Thus, the features defined as "first" and "second" can explicitly or implicitly include at least one of the features. In the description of the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0023] At present, in the field of wind power, structural adhesive is generally used as adhesive in the mold bonding process during the manufacturing process of wind turbine blades. Structural adhesive is also generally called "mold bonding adhesive". Most of the structural adhesives used for blades are epoxy structural adhesives based on epoxy resin.

[0024] In wind turbine blades, epoxy structural adhesive is mainly distributed on the joint surface between the two skins and the joint surface between the skin and the web. Epoxy structural adhesive plays the following two roles in the production of wind turbine blades:

[0025] 1) The girder and web of the wind turbine blade are connected into a whole to form an I-beam which is the main load-bearing body.

[0026] 2) The two skins are connected into a whole to form a blade shape structure that performs the power generation function.

[0027] Epoxy structural adhesives usually include component A and component B, of which component A currently often uses hydrophobic fumed silica or ordinary fumed silica as a thixotropic agent. There are a large number of weak interfaces in the structural adhesive body, which is easily damaged under cyclic stress. The thixotropic effect of ordinary fumed silica is extremely poor. The surface of hydrophobic fumed silica lacks active groups, and the bonding force between the resin and the silica surface is poor. When the amount of silica added is too large, it cannot be fully dispersed in the structural adhesive, thereby forming a large number of interface defects. During the tensile fatigue process, cracking is easily induced. The existing structural adhesive uses hydrophobic fumed silica or ordinary fumed silica as a thixotropic agent in its component A, resulting in poor bonding interface performance and high cost during the use of wind turbine blades.

[0028] In order to solve the above problems, an embodiment of the present invention provides a structural adhesive, in which component A of the structural adhesive adopts a relatively low content of hydrophilic fumed silica thixotropic agent and a thixotropic aid, thereby improving the tensile shear performance of the structural adhesive and reducing the cost of the structural adhesive.

[0029] The structural adhesive provided by the present invention is first introduced below.

[0030] According to the present application, the structural adhesive includes component A and component B, and the mass ratio of component A to component B in the structural adhesive is 100:(35~45), wherein, based on the total mass of component A, component A includes a thixotropic agent: 1wt%~2wt%; a silane coupling agent: 0.8wt%~1.2wt%; a hydrophilic fumed silica: 2.5wt%~3wt%; and other components. For example, the mass ratio of component A to component B can be 100:35, 100:36, 100:37, 100:38, 100:39, 100:40, 100:41, 100:42, 100:43, 100:44, 100:45, or any combination of the above numerical values; the mass percentage of the thixotropic agent in component A can be 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, or more. The mass percentage of the silane coupling agent in component A can be 0.80wt%, 0.85wt%, 0.90wt%, 0.95wt%, 1.00wt%, 1.05wt%, 1.10wt%, 1.15wt%, 1.20wt%, or any combination of the above values; the mass percentage of the hydrophilic fumed silica in component A can be 2.5wt%, 2.55wt%, 2.60wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3wt%, or any combination of the above values.

[0031] The inventors have found that the hydrophilic fumed silica used in the present application and the ratio of the hydrophilic fumed silica, the silane coupling agent and the thixotropic agent are adjusted to the thixotropic agent: 1wt% to 2wt%, the silane coupling agent: 0.8wt% to 1.2wt%, the hydrophilic fumed silica: 2.5wt% to 3wt% to produce a good synergistic effect, which improves the tensile and shear properties of the structural adhesive. At the same time, compared with the at least 8wt% silica in the existing structural adhesive, the silica content of the present application is lower, which can reduce the overall cost of the structural adhesive.

[0032] Thixotropic agents can help or promote the thixotropy of hydrophilic fumed silica and build bridges between thixotropic agents to increase the performance of the thixotropic agents. The large number of hydrophilic functional groups on the surface of hydrophilic fumed silica can form a large number of hydrogen bonds with epoxy resins to improve the performance of structural adhesives.

[0033] In some embodiments, the hydrophilic fumed silica is hydroxyl-modified fumed silica, and the structural schematic diagram of the hydroxyl-modified fumed silica can be as follows: Figure 1 As shown; the tensile and compressive fatigue m value of the structural adhesive is ≥12.5, and / or, when the number of cycles is tens of millions, the tensile stress amplitude of the structural adhesive is ≥56MPa.

[0034] In some of the above specific embodiments, the compressive fatigue resistance and tensile stress amplitude of the structural adhesive of the present application are significantly better than those of existing structural adhesives.

[0035] In some embodiments, the silane coupling agent is KH560; and / or, the auxiliary thixotropic agent is a polyhydroxy compound, preferably, the auxiliary thixotropic agent is one or more of trimethylolpropane propylene glycol ether, ethylene glycol, diethylene glycol, glycerol, triethylene glycol, tetraethylene glycol, and dipropylene glycol. For example, the auxiliary thixotropic agent can be trimethylolpropane propylene glycol ether, ethylene glycol, diethylene glycol, glycerol, triethylene glycol, tetraethylene glycol, dipropylene glycol, a mixture of trimethylolpropane propylene glycol ether and diethylene glycol in any proportion, a mixture of trimethylolpropane propylene glycol, ethylene glycol, and diethylene glycol in any proportion, or a mixture of ethylene glycol, glycerol, triethylene glycol, and dipropylene glycol in any proportion.

[0036] In some specific embodiments, based on the total weight of component A, component A may further include bisphenol A epoxy resin: 55 wt% to 60 wt%; bisphenol F epoxy resin: 28 wt% to 33 wt%; and diluent: 7 wt% to 13 wt%. For example, the weight percentage of bisphenol A epoxy resin in component A may be 55 wt%, 55.5 wt%, 56 wt%, 57 wt%, 58 wt%, 59 wt%, 60 wt%, or any combination of the above values, the weight percentage of bisphenol F epoxy resin in component A may be 28 wt%, 28.5 wt%, 29 wt%, 30 wt%, 31 wt%, 32 wt%, or any combination of the above values, and the weight percentage of diluent in component A may be 7 wt%, 7.5 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, or any combination of the above values.

[0037] In some specific embodiments, the bisphenol A epoxy resin is a low molecular weight bisphenol A epoxy resin, preferably, the low molecular weight bisphenol A epoxy resin is bisphenol A diglycidyl ether; and / or, the bisphenol F epoxy resin is a low molecular weight bisphenol F epoxy resin, preferably, the low molecular weight bisphenol F epoxy resin is bisphenol F diglycidyl ether; and / or, the diluent is a glycol diglycidyl ether, preferably, the diluent is butanediol diglycidyl ether and / or cyclohexanediol diglycidyl ether, for example, the diluent can be butanediol diglycidyl ether, cyclohexanediol diglycidyl ether or a mixture of butanediol diglycidyl ether and cyclohexanediol diglycidyl ether in any proportion.

[0038] In some specific embodiments, based on the total mass of component B, component B includes 30 wt% to 32 wt% of polyetheramine, 20 wt% to 22 wt% of aminopolyamide, 11 wt% to 13 wt% of heat-resistant amine-IPDA, 29 wt% to 31 wt% of toughening agent, and 4 wt% to 6 wt% of fumed silica. For example, the mass percentage of polyetheramine in component B can be 30 wt%, 30.2 wt%, 30.5 wt%, 30.8 wt%, 31 wt%, 31.5 wt%, 32 wt%, or any combination of the above values, the mass percentage of aminopolyamide in component B can be 20 wt%, 20.2 wt%, 20.5 wt%, 20.8 wt%, 21 wt%, 21.5 wt%, 22 wt%, or any combination of the above values, and the mass percentage of heat-resistant amine-IPDA in component B can be 11 wt%, 11.2 wt%, 11.6 wt%, 11.8 wt%, 11.9 wt%, 11.9 wt%, 11.8 wt%, 11.9 wt%, 11.9 wt%, 11.9 wt%, 11.9 wt%, 11.9 wt%, 11.9 wt%, 11.9 wt%, 11.9 wt%, 11.9 wt%, 11.9 wt%, 11.9 wt%, 11.9 wt%, .5wt%, 11.8wt%, 12wt%, 12.5wt%, 13wt%, or any combination range of the above values, the mass percentage of the toughening agent in component B can be 29wt%, 29.2wt%, 29.5wt%, 29.8wt%, 30wt%, 30.5wt%, 31wt%, or any combination range of the above values, and the mass percentage of fumed silica in component B can be 4wt%, 4.2wt%, 4.5wt%, 4.8wt%, 5wt%, 5.5wt%, 6wt%, or any combination range of the above values.

[0039] In some specific embodiments, the polyetheramine is a polyetheramine with a functionality ≥ 4, preferably D230 and / or T403, for example, the polyetheramine can be D230, T403 or a mixture of D230 and T403 in any proportion; and / or, the toughening agent is one or more of a core-shell polymer toughening agent, a carboxyl-terminated nitrile rubber, an amino-terminated nitrile rubber, an amino-terminated polyether (high molecular weight polyetheramine), an amino-terminated butyl rubber or a polyurethane toughening agent, preferably polyetheramine T-5000; and / or, the fumed silica is a hydrophilic fumed silica.

[0040] In a second aspect, the present application provides a method for preparing a structural adhesive, wherein component A is prepared by the following method:

[0041] The thixotropic agent, the silane coupling agent and other components in component A are mixed to obtain a mixture;

[0042] The hydrophilic fumed silica is added to the mixture several times for dispersion treatment to obtain component A.

[0043] In some specific embodiments, hydrophilic fumed silica is added to the mixture in multiple times for dispersion treatment. In the step of obtaining component A, the mass of hydrophilic fumed silica added each time does not exceed 0.3% of the total mass of component A, for example, it can be 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, or any combination of the above values; and / or, each time the hydrophilic fumed silica is added, dispersion treatment is performed, and the next hydrophilic fumed silica is added after it is fully dispersed.

[0044] In a third aspect, the present application provides a wind turbine blade, wherein the wind turbine blade is prepared using the structural adhesive of the first aspect and / or the structural adhesive prepared by the preparation method of the second aspect.

[0045] The following examples describe the present disclosure in more detail, and these examples are intended for illustrative purposes only.

[0046] In this specific embodiment, the tensile and compressive fatigue (R=-1) test is carried out according to ISO13003-2003 standard at 23±2° C. and 50±10% humidity.

[0047] Example 1

[0048] A structural adhesive comprises component A and component B, wherein the mass ratio of component A to component B is 100:43, wherein:

[0049] Component A includes 58 wt% of bisphenol A diglycidyl ether, 29 wt% of bisphenol F diglycidyl ether, 8 wt% of butanediol diglycidyl ether, 1.5 wt% of trimethylolpropane propylene glycol ether, 1 wt% of KH560 and 2.5 wt% of hydroxyl-modified fumed silica.

[0050] Component A is prepared by the following method: bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, butanediol diglycidyl, KH560, and trimethylolpropane propylene glycol ether are uniformly mixed, and hydrophilic fumed silica is continuously added in small amounts and multiple times, and the hydrophilic fumed silica is added to the mixture in multiple times for dispersion treatment. In the step of obtaining component A, the mass of the hydrophilic fumed silica added each time does not exceed 0.3% of the total mass of component A, and dispersion treatment is performed after each addition of the hydrophilic fumed silica, and the next addition of the hydrophilic fumed silica is performed after the hydrophilic fumed silica is fully dispersed.

[0051] Component B includes 31.5 wt % of polyetheramine, 21 wt % of aminopolyamide, 11.9 wt % of heat-resistant amine-IPDA, 30 wt % of polyetheramine T-5000, and 5.6 wt % of hydroxyl-modified fumed silica.

[0052] The tensile and compressive fatigue test was performed on the structural adhesive of this embodiment. The tensile and compressive fatigue (R=-1) performance was tested according to the ISO 13003-2003 standard. Under the 95% confidence interval, the tensile and compressive fatigue m value of the structural adhesive was 12.7, and the number of cycles N=10 7 (tens of millions of times), the tensile stress amplitude of the structural adhesive is 56.17MPa.

[0053] Example 2

[0054] A structural adhesive comprises component A and component B, wherein the mass ratio of component A to component B is 100:43, wherein:

[0055] The A component includes 57.6 wt % of bisphenol A diglycidyl ether, 29 wt % of bisphenol F diglycidyl ether, 8 wt % of butanediol diglycidyl ether, 1.6 wt % of trimethylolpropane propylene glycol ether, 1 wt % of KH560 and 2.8 wt % of hydroxyl-modified fumed silica.

[0056] Component A is prepared by the following method: bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, butanediol diglycidyl, KH560, and trimethylolpropane propylene glycol ether are uniformly mixed, and hydrophilic fumed silica is continuously added in small amounts and multiple times, and the hydrophilic fumed silica is added to the mixture in multiple times for dispersion treatment. In the step of obtaining component A, the mass of the hydrophilic fumed silica added each time does not exceed 0.3% of the total mass of component A, and dispersion treatment is performed after each addition of the hydrophilic fumed silica, and the next addition of the hydrophilic fumed silica is performed after the hydrophilic fumed silica is fully dispersed.

[0057] Component B includes 31.5 wt % of polyetheramine, 21 wt % of aminopolyamide, 11.9 wt % of heat-resistant amine-IPDA, 30 wt % of polyetheramine T-5000, and 5.6 wt % of hydroxyl-modified fumed silica.

[0058] The tensile and compressive fatigue test was performed on the structural adhesive of this embodiment. The tensile and compressive fatigue (R=-1) performance was tested according to the ISO 13003-2003 standard. Under the 95% confidence interval, the tensile and compressive fatigue m value of the structural adhesive was 13.3, and the number of cycles N=10 7 (tens of millions of times), the tensile stress amplitude of the structural adhesive is 57.06MPa.

[0059] Example 3

[0060] A structural adhesive comprises component A and component B, wherein the mass ratio of component A to component B is 100:43, wherein:

[0061] The A component includes 57 wt % of bisphenol A diglycidyl ether, 29 wt % of bisphenol F diglycidyl ether, 8 wt % of butanediol diglycidyl ether, 2 wt % of trimethylolpropane propylene glycol ether, 1 wt % of KH560 and 3 wt % of hydroxyl-modified fumed silica.

[0062] Component A is prepared by the following method: bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, butanediol diglycidyl, KH560, and trimethylolpropane propylene glycol ether are uniformly mixed, and hydrophilic fumed silica is continuously added in small amounts and multiple times, and the hydrophilic fumed silica is added to the mixture in multiple times for dispersion treatment. In the step of obtaining component A, the mass of the hydrophilic fumed silica added each time does not exceed 0.3% of the total mass of component A, and dispersion treatment is performed after each addition of the hydrophilic fumed silica, and the next addition of the hydrophilic fumed silica is performed after the hydrophilic fumed silica is fully dispersed.

[0063] Component B includes 31.5 wt % of polyetheramine, 21 wt % of aminopolyamide, 11.9 wt % of heat-resistant amine-IPDA, 30 wt % of polyetheramine T-5000, and 5.6 wt % of hydroxyl-modified fumed silica.

[0064] The tensile and compressive fatigue test was performed on the structural adhesive of this embodiment. The tensile and compressive fatigue (R=-1) performance was tested according to the ISO 13003-2003 standard. Under the 95% confidence interval, the tensile and compressive fatigue m value of the structural adhesive was 14, and the number of cycles N=10 7 (tens of millions of times), the tensile stress amplitude of the structural adhesive is 56.84MPa.

[0065] Comparative Example 1

[0066] A structural adhesive comprises component A and component B, wherein the mass ratio of component A to component B is 100:43, wherein:

[0067] The A component includes 59.9 wt % of bisphenol A diglycidyl ether, 29 wt % of bisphenol F diglycidyl ether, 8 wt % of butanediol diglycidyl ether, 0.6 wt % of trimethylolpropane propylene glycol ether, 1 wt % of KH560 and 1.5 wt % of hydroxyl-modified fumed silica.

[0068] Component B includes 31.5 wt % of polyetheramine, 21 wt % of aminopolyamide, 11.9 wt % of heat-resistant amine-IPDA, 30 wt % of polyetheramine T-5000, and 5.6 wt % of hydroxyl-modified fumed silica.

[0069] The structural adhesive of this comparative example was subjected to a tensile and compressive fatigue test. The tensile and compressive fatigue (R=-1) performance was tested in accordance with the ISO 13003-2003 standard. Under a 95% confidence interval, the tensile and compressive fatigue m value of the structural adhesive was 9.8. When the number of cycles N=107 (million times), the tensile stress amplitude of the structural adhesive was 54.20 MPa.

[0070] Comparative Example 2

[0071] A structural adhesive comprises component A and component B, wherein the mass ratio of component A to component B is 100:43, wherein:

[0072] The A component includes 59.6 wt % of bisphenol A diglycidyl ether, 30 wt % of bisphenol F diglycidyl ether, 8 wt % of butanediol diglycidyl ether, 0.4 wt % of trimethylolpropane propylene glycol ether, 1 wt % of KH560 and 1 wt % of hydroxyl-modified fumed silica.

[0073] Component B includes 31.5 wt % of polyetheramine, 21 wt % of aminopolyamide, 11.9 wt % of heat-resistant amine-IPDA, 30 wt % of polyetheramine T-5000, and 5.6 wt % of hydroxyl-modified fumed silica.

[0074] The structural adhesive of this comparative example was subjected to a tensile and compressive fatigue test. The tensile and compressive fatigue (R=-1) performance was tested in accordance with the ISO 13003-2003 standard. Under a 95% confidence interval, the tensile and compressive fatigue m value of the structural adhesive was 9.1. When the number of cycles N=107 (million times), the tensile stress amplitude of the structural adhesive was 54.88 MPa.

[0075] Comparative Example 3

[0076] A structural adhesive comprises component A and component B, wherein the mass ratio of component A to component B is 100:43, wherein:

[0077] The A component includes 54.3 wt % of bisphenol A diglycidyl ether, 30 wt % of bisphenol F diglycidyl ether, 8 wt % of butanediol diglycidyl, 2.7 wt % of trimethylolpropane propylene glycol ether, 1 wt % of KH560 and 4 wt % of hydroxyl-modified fumed silica.

[0078] Component B includes 31.5 wt % of polyetheramine, 21 wt % of aminopolyamide, 11.9 wt % of heat-resistant amine-IPDA, 30 wt % of polyetheramine T-5000, and 5.6 wt % of hydroxyl-modified fumed silica.

[0079] The structural adhesive of this comparative example was subjected to a tensile and compressive fatigue test. The tensile and compressive fatigue (R=-1) performance was tested in accordance with the ISO 13003-2003 standard. Under a 95% confidence interval, the tensile and compressive fatigue m value of the structural adhesive was 10.4. When the number of cycles N=107 (million times), the tensile stress amplitude of the structural adhesive was 55.01 MPa.

[0080] Comparative Example 4

[0081] A structural adhesive comprises component A and component B, wherein the mass ratio of component A to component B is 100:43, wherein:

[0082] The A component includes 55 wt % of bisphenol A diglycidyl ether, 28 wt % of bisphenol F diglycidyl ether, 9 wt % of butanediol diglycidyl ether and 8 wt % of fumed silica.

[0083] Component B includes 31.5 wt % of polyetheramine, 21 wt % of aminopolyamide, 11.9 wt % of heat-resistant amine-IPDA, 30 wt % of polyetheramine T-5000, and 5.6 wt % of hydroxyl-modified fumed silica.

[0084] The structural adhesive of this comparative example was subjected to a tensile and compressive fatigue test. The tensile and compressive fatigue (R=-1) performance was tested in accordance with the ISO 13003-2003 standard. Under a 95% confidence interval, the tensile and compressive fatigue m value of the structural adhesive was 8.9. When the number of cycles N=107 (million times), the tensile stress amplitude of the structural adhesive was 53.97 MPa.

[0085] Because various modifications and variations are obvious to those skilled in the art within the scope of the present disclosure. Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all raw materials used in the examples are commercially available or prepared according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.

[0086] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A structural adhesive, characterized in that: The invention comprises component A and component B, wherein the mass ratio of component A to component B in the structural adhesive is 100:(35-45), wherein, based on the total mass of component A, component A comprises: Thixotropic agent: 1wt%-2wt%, silane coupling agent: 0.8wt%-1.2wt%, hydrophilic fumed silica: 2.5wt%-3wt%, and other components.

2. The structural adhesive according to claim 1, characterized in that: The hydrophilic fumed silica is hydroxyl-modified fumed silica; The tensile-compression fatigue m value of the structural adhesive is ≥12.5, and / or, when the number of cycles is tens of millions, the tensile stress amplitude of the structural adhesive is ≥56 MPa.

3. The structural adhesive according to claim 1, characterized in that: The silane coupling agent is KH560; And / or, the auxiliary thixotropic agent is a polyhydroxy compound, preferably, the auxiliary thixotropic agent is one or more of trimethylolpropane propylene glycol ether, ethylene glycol, diethylene glycol, glycerol, triethylene glycol, tetraethylene glycol, and dipropylene glycol.

4. The structural adhesive according to claim 1, characterized in that: Based on the total mass of the A component, the A component further comprises: Bisphenol A epoxy resin: 55wt% to 60wt%, bisphenol F epoxy resin: 28wt% to 33wt%, diluent: 7wt% to 13wt%.

5. The structural adhesive according to claim 4, characterized in that: The bisphenol A epoxy resin is a low molecular weight bisphenol A epoxy resin, and preferably, the low molecular weight bisphenol A epoxy resin is bisphenol A diglycidyl ether; And / or, the bisphenol F epoxy resin is a low molecular weight bisphenol F epoxy resin, preferably, the low molecular weight bisphenol F epoxy resin is bisphenol F diglycidyl ether; And / or, the diluent is glycol diglycidyl ether, preferably, the diluent is butanediol diglycidyl ether and / or cyclohexanediol diglycidyl ether.

6. The structural adhesive according to claim 1, characterized in that: Based on the total mass of the B component, the B component includes: Polyetheramine: 30wt% to 32wt%, aminopolyamide: 20wt% to 22wt%, heat-resistant amine-IPDA: 11wt% to 13wt%, toughening agent: 29wt% to 31wt%, fumed silica: 4wt% to 6wt%.

7. The structural adhesive according to claim 6, characterized in that: The polyetheramine is a polyetheramine with a functionality ≥ 4, preferably D230 and / or T403; and / or, the toughening agent is one or more of a core-shell polymer toughening agent, a carboxyl-terminated nitrile rubber, an amino-terminated nitrile rubber, an amino-terminated polyether, an amino-terminated butyl rubber or a polyurethane toughening agent, preferably polyetheramine T-5000; And / or, the fumed silica is hydrophilic fumed silica.

8. A method for preparing a structural adhesive according to any one of claims 1 to 7, characterized in that: Component A was prepared by the following method: The thixotropic agent, the silane coupling agent and other components in component A are mixed to obtain a mixture; The hydrophilic fumed silica is added to the mixed material several times for dispersion treatment to obtain the A component.

9. The preparation method according to claim 8, characterized in that: In the step of adding the hydrophilic fumed silica to the mixed material for dispersion treatment multiple times to obtain the component A, the mass of the hydrophilic fumed silica added each time does not exceed 0.3% of the total mass of the component A; And / or, each time the hydrophilic fumed silica is added, a dispersion treatment is performed, and the next addition of the hydrophilic fumed silica is performed after the hydrophilic fumed silica is fully dispersed.

10. A wind turbine blade, characterized in that: The preparation process uses the structural adhesive described in any one of claims 1 to 7 and / or the preparation process uses the structural adhesive prepared by the preparation method described in any one of claims 8 to 9.

Citation Information

Patent Citations

  • High-strength wind energy blade splicing structural adhesive

    CN102492387A

  • Epoxy resin adhesive for bonding rubber materials and formula thereof

    CN111518498A

  • Preparation method of modified silicon dioxide-epoxy resin composite slurry

    CN114292614A

  • High-performance epoxy glue and application thereof in silk-screen printing

    CN116445116A

  • Epoxy resin adhesive and preparation method thereof

    CN117025151A